Candidate Regulators of Dyslipidemia in Chromosome 1 Substitution Lines Using Liver Co-Expression Profiling Analysis - Xu, Fuyi; Wang, Maochun; Hu, Shixian; Zhou, Yuxun; Collyer, John; Li, Kai; Xu, Hongyan; Xiao, Junhua (Frontiers in Genetics, 2020)
Dyslipidemia is the major risk factor of cardiovascular disease. Although many genetic factors have been unveiled, large fraction of the phenotypic variance still needs further investigation. Chromosome 1 (Chr 1) harbors multiple gene loci related to blood lipid regulation, nevertheless, it’s challenging to identify the functional genes. We constructed a mouse population, chromosome 1 substitution lines (C1SLs), of which Chr 1 differ from recipient C57BL/6J (B6) mouse while others remain the same. Therefore, any phenotype variance between C1SLs and B6 can be easily inferred to Chr 1. In the current study, we assayed plasma lipid and glucose levels in 13 C1SLs and their recipient strain B6. Through weighted gene co-expression network analysis of the liver transcriptome and “guilty-by-association” study, eight associated modules of plasma lipid and glucose were identified. Further joint analysis of human genome wide association studies revealed 48 candidate genes. In addition, 38 genes on Chr 1 were also uncovered, in which 13 have been functional validated in mouse models. These results suggest that C1SLs are ideal mouse models to study the complex traits and identify the functional genes on Chr 1 with gene co-expression network analysis.